DETERMINING THE TYPES AND SEVERITY OF VIOLENCE AGAINST WOMEN IN AFGHANISTAN - Palwasha, Seraj (Interdisciplinary Approaches to Medicine, 2021)
Violence has a negative impact on various aspects of women’s health, including quality of life, social functioning, physical health and is one of the most considerate human rights issues in Afghanistan. The aim of this study: to determine the anatomical parts, types and severity of injuries in cases of violence against women in Afghanistan.Тhis study is an Analytic Cross-sectional study. Primary data containing information referring to cases of violence against women registered from January 2019 to January 2021 were extracted from Afghanistan Forensic Science Organization. The scope of interest in this study was females over the age of 18 and they were inclusive of Afghan women.Нe average age of women was 22.3 and more than 80% of them had primary and secondary education; this study shows in 2019 the most injuries were limbs and nervous injury was only one case. (table 1) In 2020 most injuries were limbs and nervous injury was only one case. (table 1) Table 2 shows that most of injuries were moderate level and mild injuries were the next and severe injuries with 20 cases was last of this rank. In 2020 most of them were moderate level and after that was mild and severe level. In additional, Type of injuries in 2019 shows that 38.2% of injuries was blunt, 4.9% sharp, 2.2 thermal and 0.02% was unclear. In 2020 blunt injuries was the first injuries and unlike 2019 weapon reported as injures types (table 3).With the passage of time and the civilization, the intellectual levels of individuals in society increased and the thinkers of societies became more prominent in the presence of women alongside men, so women were considered complementary to men, and this was the beginning of changing women’s status.